Deep Dyspareunia and Sexual Quality of Life in Women With Endometriosis - Leona K. Shum, BSc(Hons) (Sexual Medicine, 2018)
Introduction: Deep dyspareunia occurs in half of women with endometriosis, a condition present in 10% of reproductive-age women and associated with negative effects on sexual quality of life (SQoL). However, women with endometriosis can have other clinical factors (eg, superficial dyspareunia, other pelvic pains, and psychological or pain conditions) possibly affecting SQoL. Aims: To determine whether deep dyspareunia is associated with SQoL in women with endometriosis, independent of potential confounders. Methods: This study involved a prospective patient registry of women at a tertiary-level referral center for endometriosis and pelvic pain. Inclusion criteria were (i) referrals to the center recruited into the registry from January 2014 through December 2016 and (ii) subsequent surgery at the center with histologic confirmation of endometriosis. Exclusion criteria included menopausal status, age at least 50 years, never sexually active, or did not answer dyspareunia or SQoL questions. Bi-variable tests and multiple linear regression analysis were performed. Main Outcome Measures: SQoL measured by the 5-item sexual intercourse subscale of the Endometriosis Health Profile-30 (EHP-30) modular questionnaire (0–100%, with higher scores indicating worse SQoL). Results: Consent rate for the prospective registry was 87%; 277 women met the study criteria (mean age = 34.2 ± 7.1 years). Most women had stage I to II endometriosis at time of surgery (64%), with the remaining having stage III to IV endometriosis. Through regression analysis, worse SQoL (higher EHP-30 sexual intercourse subscale score) was independently associated with: more severe deep dyspareunia (P < .0001), more severe superficial dyspareunia (P < .0001), increased depression (P < .001), higher pain catastrophizing (P = .04), bladder pain syndrome (P = .02), heterosexual orientation (P < .001), and new referral status (P = .02). Conclusion: In women with endometriosis at a tertiary referral center, more severe deep dyspareunia was associated with worse SQoL, independent of superficial dyspareunia, psychological comorbidities, and other potential confounders.Shum LK, Bedaiwy MA, Allaire C, et al. Deep Dyspareunia and Sexual Quality of Life in Women With Endometriosis. Sex Med 2018;6:224–233. Key Words: Deep Dyspareunia, Endometriosis, Sexual Quality of Life, Superficial Dyspareunia